GR_GERICHTE SK1 2021 85 vom 22. März 2023 , 9C_284/2024 vom 12.06.2024 - GR Gerichte (2023)
Verbrechen gegen das Betäubungsmittelgesetz gem. Art. 19 Abs. 2 lit. a BetmG etc. | Betäubungsmittelgesetz BetmG